Pengambilan Keputusan Melalui Strategi Komunikasi Efektif pada Keluarga Pasien Kritis - Suhartini, Suhartini; Lahati, Nurul Safira; Anggorowati, Anggorowati (Journal of Telenursing (JOTING), 2023)
This study aims to determine effective communication strategies with the families of patients receiving treatment in the ICU. The method used is a scoping review using Arksey and O'Malley model analysis. A systematic search was carried out using database bases, namely Sciencedirect, Scopus, Proquest. The research results show that there are three categories, namely family-centered care, special aspects of communication and structured family communication guidelines. In conclusion, an effective communication approach with family members in the Intensive Care Unit provides a very important role for critical patient-centered care in the intensive care unit. Keywords: Intensive Care Unit, Family, Communication